2017
DOI: 10.1111/jvp.12406
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of nebulized and subcutaneously implanted terbinafine in cottonmouths (Agkistrodon piscivorus)

Abstract: Ophidiomyces ophiodiicola, the causative agent of snake fungal disease, is proposed as a serious threat to the conservation of several snake populations. The objective of this study was to determine the pharmacokinetic parameters of terbinafine administered through nebulization and a sustained subcutaneous implant as potential treatments of Ophidiomyces in reptiles. Seven adult cottonmouths (Agkistrodon piscivorus) were used in single-dose trials. Each snake was nebulized with terbinafine (2 mg/ml) for 30 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Previous studies have demonstrated that nebulisation is effective in treating ophidiomycosis. 7 Fusarium spp. are ubiquitous soil saprophytes and were found in the freshly shed skins of 4% of 127 captive squamate reptiles surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that nebulisation is effective in treating ophidiomycosis. 7 Fusarium spp. are ubiquitous soil saprophytes and were found in the freshly shed skins of 4% of 127 captive squamate reptiles surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…Reported MIC values suggest that Emydomyces is susceptible to antifungal drugs commonly used in the treatment of reptilian fungal infections, such as itraconazole, voriconazole, and terbinafine (4,30). However, only a few studies evaluating the safety, efficacy, and pharmacokinetics of these antifungal drugs have been performed in a limited selection of reptile species (30)(31)(32). Toxicity associated with voriconazole administration has been reported in at least one species of snake with clinically relevant dosages (30).…”
Section: Discussionmentioning
confidence: 99%
“…The snake was treated with terbinafine (Terbinafine, 250 mg; InvaGen Pharmaceuticals, Hauppauge, NY, USA) via nebulisation at 2 mg/ml for 30 minutes every 24 hours from 21 July 2015 to 19 August 2015 6. In October 2015, following nebulisation treatment, the animal was negative for O ophiodiicola on qPCR.…”
Section: Treatmentmentioning
confidence: 99%